THE ROLE OF PUBLIC RELATIONS DIRECTORATE GENERAL OF IMMIGRATION IN THE POLICY OF BANNING FOREIGN NATIONALS FROM ENTERING THE TERRITORY OF INDONESIA - Riri Ardyaningtyas; Guntur Widyanto (Polteknik Imigrasi, 2021)
The mutation of the Covid-19 virus in various countries has made the Indonesian Government issue various public policies related to the entry and exit of foreigners both from and to Indonesian territory. The Directorate General of Immigration as the authorized agency in the service of visas and stay permits, issued several public policies during the pandemic, especially related to the entry ban of foreigners. Including when the Covid-19 case in India increased significantly, a policy was imposed to prohibit the entry of foreigners from India. Public Relations of the Directorate General of Immigration is also involved not only in policy making, where aspirations from the public are accommodated and then conveyed to policy makers, but also in disseminating established policies in the form of information that is easily understood by the public.